Evaluation of a standardised Vi poly-l-lysine ELISA for serology of Vi capsular polysaccharide antibodies. (July 2020) - Rigsby, Peter; Beamish, Emma; Hockley, Jason; Atkinson, Eleanor; Hitri, Krisztina; Jones, Elizabeth; Yang, Jae Seung; Qadri, Firdausi; Bachtiar, Novilia S.; Elias, Sean C.; Goel, Akshay; Mishra, Ravipratapnarayan; et al.
Abstract: Typhoid vaccines based on protein-conjugated capsular Vi polysaccharide (TCVs) prevent typhoid in infants and young children. Analysis of the serum anti-Vi IgG response following immunisation against typhoid confirms the immunogenicity of TCVs and forms an important part of the pathway to licensing. Comparative studies could expedite the licencing process, and the availability of a standardised ELISA method alongside the 1st International Standard (IS) 16/138 for anti-typhoid capsular Vi polysaccharide IgG (human) will facilitate this process. To this end, a non-commercial ELISA based on a coat of Vi and poly-l -lysine (Vi-PLL ELISA) was evaluated by 10 laboratories. Eight serum samples, including IS 16/138, were tested in the standardised Vi-PLL ELISA ( n  = 10), a commercial Vi ELISA ( n  = 3) and a biotinylated Vi ELISA ( n  = 1). Valid estimates of potencies relative to IS 16/138 were obtained for all samples in the Vi-PLL ELISA and the commercial ELISA, with good repeatability and reproducibility evident from the study results and concordant estimates obtained by the two ELISA methods. The study demonstrates that the Vi-PLL ELISA can be used in clinical trial studies to determine the immunogenicity of TCVs.